![image](https://tex.z-dn.net/?f=%5Clog_%7Bx%7D3%2B%5Clog_%7B3%7Dx%3D2%2C+%5C%5C+x%3E0%2C+x+%5Cneq+1%2C+%5C%5C+%5Cfrac%7B1%7D%7B%5Clog_%7B3%7Dx%7D%2B%5Clog_%7B3%7Dx-2%3D0%2C+%5C%5C+%5Cfrac%7B1%2B%5Clog_%7B3%7Dx%28%5Clog_%7B3%7Dx-2%29%7D%7B%5Clog_%7B3%7Dx%7D%3D0%2C+%5C%5C+%5Clog_%7B3%7Dx+%5Cneq+0%2C+%5C%5C+1%2B%5Clog_%7B3%7Dx%5Ccdot%5Clog_%7B3%7Dx-2%5Clog_%7B3%7Dx%3D0%2C+%5C%5C%5Clog%5E2_%7B3%7Dx-2%5Clog_%7B3%7Dx%2B1%3D0%2C+%5C%5C+%28%5Clog_%7B3%7Dx-1%29%5E2%3D0%2C+%5C%5C+%5Clog_%7B3%7Dx-1%3D0%2C+%5C%5C+%5Clog_%7B3%7Dx%3D1%2C+%5C%5C+x%3D3.)
0, x \neq 1, \\ \frac{1}{\log_{3}x}+\log_{3}x-2=0, \\ \frac{1+\log_{3}x(\log_{3}x-2)}{\log_{3}x}=0, \\ \log_{3}x \neq 0, \\ 1+\log_{3}x\cdot\log_{3}x-2\log_{3}x=0, \\\log^2_{3}x-2\log_{3}x+1=0, \\ (\log_{3}x-1)^2=0, \\ \log_{3}x-1=0, \\ \log_{3}x=1, \\ x=3." alt="\log_{x}3+\log_{3}x=2, \\ x>0, x \neq 1, \\ \frac{1}{\log_{3}x}+\log_{3}x-2=0, \\ \frac{1+\log_{3}x(\log_{3}x-2)}{\log_{3}x}=0, \\ \log_{3}x \neq 0, \\ 1+\log_{3}x\cdot\log_{3}x-2\log_{3}x=0, \\\log^2_{3}x-2\log_{3}x+1=0, \\ (\log_{3}x-1)^2=0, \\ \log_{3}x-1=0, \\ \log_{3}x=1, \\ x=3." align="absmiddle" class="latex-formula">